2016
DOI: 10.1653/024.099.0301
|View full text |Cite
|
Sign up to set email alerts
|

Juvenomimetic and Insecticidal Activities ofSenecio salignus(Asteraceae) andSalvia microphylla(Lamiaceae) onSpodoptera frugiperda(Lepidoptera: Noctuidae)

Abstract: Plant extracts can be used as an alternative to synthetic insecticides for the control of insect pests. Based on this knowledge, juvenomimetic and insecticidal activities of n-hexane extracts of the aerial parts of Senecio salignus DC. (Asteraceae) and Salvia microphylla Kunth (Lamiaceae) collected in Mexico were evaluated against 1st instar larvae of Spodoptera frugiperda Smith & Abbot (Lepidoptera: Noctuidae). Senecio salignus extract showed insecticidal activity at 500 ppm, resulting in larval mortality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
1
15
1
1
Order By: Relevance
“…The pulp and seed extracts were subjected to qualitative chemical tests to identify the presence of chemical constituents present using the following methods: (1) alkaloids: Meyer, Wagner, and Dragendorff reagents; (2) sterols and triterpenes: Liebermann/Burchard reagent; (3) tannins: ferric chloride and gelatin; (4) saponins: Bubble test; (5) flavonoids: Shinoda test; (6) coumarins: Erlich reagent; (7) anthraquinone glucosides: alkaline reaction; (8) carbohydrates: Benedict’s reagent (Cai, Shi & Gao, 2011; Tiwari et al, 2011; Romo-Asunción et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The pulp and seed extracts were subjected to qualitative chemical tests to identify the presence of chemical constituents present using the following methods: (1) alkaloids: Meyer, Wagner, and Dragendorff reagents; (2) sterols and triterpenes: Liebermann/Burchard reagent; (3) tannins: ferric chloride and gelatin; (4) saponins: Bubble test; (5) flavonoids: Shinoda test; (6) coumarins: Erlich reagent; (7) anthraquinone glucosides: alkaline reaction; (8) carbohydrates: Benedict’s reagent (Cai, Shi & Gao, 2011; Tiwari et al, 2011; Romo-Asunción et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…EOs are also valorized for their antimicrobial and antioxidant activities [28]. In addition, the literature has described the insecticidal activity of the n-hexane extracts [29]. In Algeria, this species is used in traditional medicine for some stomach ailments.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a synthetic concoction based on 0.93, 1.18, 1.82 and 1.68 µg of myristic, stearic, palmitoleic and palmitic acids, respectively, was reported to lure some insect species (Adhikary, Mukherjee, & Barik, ). Furthermore, Romo‐Asunción et al () demonstrated that palmitic acid showed insecticidal and juvenomimetic activities against Spodoptera frugiperda larvae upon exposure to 1,600 ppm of palmitic acid, with an LC 50 value of 989 ppm. In addition, Liu et al () found that palmitic acid displayed strong antifungal activity, including suppression of mycelial growth and an inhibitory effect against spore germination, which might indicate great potential for exploring alternative effective measures for controlling plant diseases.…”
Section: Discussionmentioning
confidence: 99%